The anti-anxiety drug lorazepam changes implicit behaviors but not explicit evaluations of sense of agency under authoritative pressure: A functional magnetic resonance imaging study - Chen, Chenyi; Martínez, Róger Marcelo; Chen, Yu-Chun; Fan, Yang-Teng; Cheng, Yawei (Frontiers in Psychology, 2022)
Previous research on coercion has neglected the fact that agents under authoritative pressure may also suffer from coercive power, which can trigger anxiety-like emotional negativity on its victims. Furthermore, high levels of neuroticism and/or anxiety have been found to be associated with the compliance of various forms of social pressure. In this study, we investigate the effects of the anxiolytic GABAA (gamma-Aminobutyric acid) modulator, lorazepam, on behavioral and neural responses to coercive power. Here, we applied a virtual obedience to authority paradigm alongside lorazepam administration (versus placebo), and during fMRI scanning. Our results show that lorazepam administration exerted differential effects on the reaction times (RTs) when initiating harming versus helping behaviors, with longer harming RTs compared to helping RTs, despite comparable subjective ratings regarding perceived coercion. Coercive harming significantly increased activity in the amygdala, hippocampus, orbitofrontal cortex, and dorsolateral prefrontal cortex (dlPFC). Lorazepam administration decreased amygdala and hippocampus activity, but increased dlPFC and right temporoparietal junction activations. The lower activity in the hippocampus predicted higher ratings for perceived coercion. Furthermore, lorazepam significantly decreased the functional connectivity of the hippocampus with the dlPFC during coercive harming. In conclusion, we provide evidence –by incorporating multimodal indices, including neuroimaging, neuropharmacological interventions, and behavioral assessments– to posit that the GABAA agonist, lorazepam, might aid as a possible intervention in service of coping strategies against coercion.